EFEKTIFITAS KOMUNIKASI PEMBELAJARAN ONLINE DENGAN MENGGUNAKAN MEDIA E-LEARNING PADA PERKULIAHAN BODY OTOMOTIF - Basori, Basori (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2014)
This study aims to determine the effectiveness of learning communication with e -learning models onthe Body of Automotive lecture. The course material is included in the e -learning website at FKIP UNS.The methods of this study is a qualitative methods and it is used the Ex Post Facto. The population ofthe study was all students taking the automotive concentration. Data collection was done through aquestionnaire. Data analysis was done by a descriptive.Based on the study result, we got the conclusion that: (1) the teaching material is quite understandableby students, (2) the material such as text, images, sound, and harmony in all three teaching materials can bereceived clearly by students, (3) The teaching material increases knowledge of students, (4 ) e-learning modedirects the student to agree with the teaching material, (5) e-learning mode encourages the students tocomplete the task of e-learning teaching material. In general, the study found that the delivery of coursematerial’s to students through the e-learning model’s was effective. so, we could concluded the learningcommunication is effective.